1998
DOI: 10.1083/jcb.142.2.457
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Polarity by Microtubules in Fission Yeast

Abstract: To investigate the role of microtubules in regulating cell polarity in Schizosaccharomyces pombe, we have developed a system in which normally cylindrical fission yeast synchronously form branched cells at high frequency upon treatment with the microtubule-depolymerizing drug thiabendazole (TBZ). Branching depends on both elevated temperature and cell cycle state and occurs at high frequency only when TBZ is added to cells that have not yet passed through New-End Take-Off (NETO), the normal transition from mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
2
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 71 publications
4
153
2
4
Order By: Relevance
“…This result is consistent with the hypothesis that the phenotype arises as a result of hyperstabilized microtubules, because higher temperatures generally favor microtubule assembly. A similar temperature dependence has been reported for cell morphology defects observed in cells treated with TBZ (Sawin and Nurse, 1998). Because the cell cycle mutants used here to produce long cells are all temperature sensitive, it is not possible to distinguish clearly between the effects of temperature and cell length.…”
Section: Microtubules and Cell Morphologymentioning
confidence: 57%
See 1 more Smart Citation
“…This result is consistent with the hypothesis that the phenotype arises as a result of hyperstabilized microtubules, because higher temperatures generally favor microtubule assembly. A similar temperature dependence has been reported for cell morphology defects observed in cells treated with TBZ (Sawin and Nurse, 1998). Because the cell cycle mutants used here to produce long cells are all temperature sensitive, it is not possible to distinguish clearly between the effects of temperature and cell length.…”
Section: Microtubules and Cell Morphologymentioning
confidence: 57%
“…Previous work has demonstrated that shortening microtubule length, either by mutations in tubulin or tubulin-Cofactor genes (Umesono et al, 1983;Grishchuk and McIntosh, 1999;Radcliffe et al, 1999), by the addition of TBZ (Sawin and Nurse, 1998), or by deletion of microtubule-associated proteins (mal3 ϩ , Beinhauer et al, 1997;tea2 ϩ , Browning et al, 2000;tip1 ϩ , Brunner and Nurse, 2000; dis1 ϩ and mtc1 ϩ , Nakaseko et al, 2001) leads to the formation of T-shaped cells. Results presented here suggest that an increase in microtubule length can cause bending at the growing ends of the cells, resulting in C-or J-shaped cells.…”
Section: Microtubules and Cell Morphologymentioning
confidence: 99%
“…Tea1 also functions in the microtubule cytoskeleton and is important for generating global spatial order (Mata & Nurse 1997). Recently, Sawin & Nurse developed a system in which the fission yeast cells synchronously form branched cells at high frequency following treatment with TBZ (Sawin & Nurse 1998). They also showed that branching depended on both elevated temperature and cell-cycle stage.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence of 3HA-tagged cells was performed as described previously (Bähler and Pringle, 1998), using the monoclonal HA11 primary antibody (Berkeley Antibody, Richmond, CA) and fluorescein isothiocyanate (FITC)-tagged goat anti-mouse-IgG secondary antibody (Jackson ImmunoResearch, Laboratories, West Grove, PA). Staining of F-actin with rhodamine-phalloidin (Molecular Probes, Eugene, OR) was performed using the method of Sawin and Nurse (1998) Figure 1. Identification of the fim1 start codon (see text for details).…”
Section: Morphological Observations and Latrunculin Treatmentmentioning
confidence: 99%